Innovative technology for processing saprolitic laterite ores by hydrochloric acid atmospheric pressure leaching. (February 2015) - Guo, Qiang; Qu, Jingkui; Han, Bingbing; Zhang, Peiyu; Song, Yunxia; Qi, Tao
Graphical abstract: Highlights: Atmospheric acid leaching extracts Ni and Fe under mild operating conditions. This new technology separates valuable Ni and Fe from Si and Mg in the laterite ores. This new technology can increase the grade of Ni in the hydrolyzate. This new technology reduces costs by recycling acid media and recovering waste heat. Hydrolyzate with high Ni content is a suitable raw material for ferro-nickel production. Abstract: An innovative technology for processing saprolitic laterite ores from the Philippines by hydrochloric acid atmospheric leaching and spray hydrolysis is proposed. The factors that affect the hydrochloric acid atmospheric leaching of the laterite ores and spray hydrolysis of the atmospheric acid leach solution are investigated. Experimental results show that the leaching of Ni, Fe, and Mg is 98.9 wt%, 97.8 wt%, and 80.9 wt%, respectively, under optimal acid leaching conditions. The hydrolysis of Ni and Fe by the atmospheric acid leach solution approaches 100 wt% at the temperature range of 450–500 °C. Characterization results show that a serpentine mineral, nominally Mg3 Si2 O5 (OH)4, is the major component and goethite, FeO(OH), is the minor one in the laterite ores. Treatment by hydrochloric acid atmospheric leaching breaks the mineral lattices of the laterite ores and makes amorphous silica the primary product in the atmospheric acid leach residue. The grade of Ni in the hydrolyzate increases to 4.55%. The hydrolyzate with high Ni content can be utilized for ferro-nickel production.